2021
DOI: 10.1136/jitc-2020-002058
|View full text |Cite|
|
Sign up to set email alerts
|

Fecal calprotectin concentration to assess endoscopic and histologic remission in patients with cancer with immune-mediated diarrhea and colitis

Abstract: BackgroundImmune-mediated diarrhea and colitis (IMDC) is currently diagnosed and monitored by evaluating clinical symptoms. Deep remission is determined by endoscopic and histologic evaluation of the disease process. However, repeating these invasive procedures frequently can become cumbersome. We sought to assess the role of fecal calprotectin (FC) concentration as a non-invasive biomarker of endoscopic or histologic remission.MethodsWe performed a retrospective study of patients with IMDC who were tested for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 38 publications
1
22
0
Order By: Relevance
“…Accordingly, levels of fecal calprotectin and lactoferrin correlate with endoscopic findings of ulceration and histological signs of IMC (107). Furthermore, fecal calprotectin is increased upon the onset of diarrhea and reduced when clinical remission is observed (108,109). This could therefore be a promising marker to monitor disease activity and relapse in patients, as already suggested in American Society of Clinical Oncology guidelines (110).…”
Section: Cellular Indicatorsmentioning
confidence: 82%
“…Accordingly, levels of fecal calprotectin and lactoferrin correlate with endoscopic findings of ulceration and histological signs of IMC (107). Furthermore, fecal calprotectin is increased upon the onset of diarrhea and reduced when clinical remission is observed (108,109). This could therefore be a promising marker to monitor disease activity and relapse in patients, as already suggested in American Society of Clinical Oncology guidelines (110).…”
Section: Cellular Indicatorsmentioning
confidence: 82%
“…Colonoscopy may still be useful in patients with treatment-refractory IMC as the presence of gross abnormalities in the proximal colon and persistent histologic evidence of IMC can inform the clinician's decision to initiate biologic therapy early in the treatment course. 7 Non-invasive biomarkers such as fecal calprotectin and lactoferrin have demonstrated utility in confirming the diagnosis of IMC [9][10][11] ; however, they are not routinely used to guide treatment. In addition, these biomarkers may not help identify alternative structural causes of gastrointestinal symptoms such as IMC with superimposed infection.…”
Section: Discussionmentioning
confidence: 99%
“…8 Furthermore, the diagnosis of IMC is often made clinically by the treating oncologist based on the presence of symptoms and as such, treatment with steroids is initiated without histological confirmation of the IMC diagnosis or use of non-invasive biomarkers such as fecal calprotectin or lactoferrin. [9][10][11] This common clinical scenario has the potential for missing alternative diagnoses such as infectious or radiation colitis and can lead to delays in escalation of therapy due to missed severe disease. 4,12 Endoscopic testing for IMC varies widely in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…We found two patients with CIC had elevated fecal calprotectin (Figure 3C). Zou et al (159) retrospectively analyzed the fecal calprotectin of patients with CIC and found that it was increased at the onset of IMC while decreased after treatment. In terms of infectious pathogens, Clostridium difficile (C. difficile) was the most common pathogen.…”
Section: Laboratory Featuresmentioning
confidence: 99%
“…LDH ≥618 IU/L was related to a poor prognosis in CIC patients (60). Conversely, the decrease of fecal calcitonin after treatment occurred more significantly in patients with CIC remission under endoscopy, which could be used as a non-invasive tool for monitoring and evaluating the response of CIC (159). Nevertheless, the value of fecal calcitonin was limited by its 54% specificity in predicting the endoscopic remission of CIC (166).…”
Section: Prognosismentioning
confidence: 99%